Estimating Economies of scale in Chinese commercial banks - WANG, WEI-TING (2016)
This study adopt a parametric approach which is stochastic frontier analysis on the basis of tranlog cost function to measure the economies of scale in Chinese banking industry. The data set is collected from BankScope during 2007 to 2014 and use 60 commercial banks comprising 5 state-owned commercial banks and other 55 commercial banks as random effect panel data. The purpose of this study is to evaluate the economies of scale between state-owned commercial banks and other commercial banks from 2007 to 2014 and in the end of the study will provide some future suggestions to policymakers or future researchers. The findings demonstrate that state-owned commercial banks exist diseconomies of scale, while other commercial banks exist economies of scale. Although state-owned commercial banks appear diseconomies of scale, both types of commercial banks are indeed making progress on the aspect of operation efficiency and management efficiency since both values of SCALE gradually decline from 2007 to 2014.